Experimental and Simulation Analysis of Natural Gas-Diesel Combustion in Dual-Fuel Engines - Dimitriou, Pavlos; Tsujimura, Taku; Kojima, Hirokazu; Aoyagi, Kenji; Kurimoto, Naoki; Nishijima, Yoshiaki (Frontiers in Mechanical Engineering, 2020)
The recent strict emission regulations and the necessity to reduce the global CO2 levels have promoted research studies over alternative fuel combustion technologies. Dual fuel technology is a fascinating approach as it could combine the benefits of two fuels to achieve high thermal efficiency with lower harmful emissions. Natural gas burns cleaner than other fossil fuels and its recent low price makes it an attractive fuel as a near-term solution. The utilization of natural gas with diesel in a compression ignition engine can result in high engine performance with lower CO2 emissions. However, at low engine loads, natural gas-diesel operation suffers from low combustion efficiency with high unburned hydrocarbon and carbon monoxide emissions. The present paper collates the work of experimental and simulation studies on natural gas-diesel dual fuel operation over three different engine set-ups. Two single-cylinder, with and without optical access, and a multi-cylinder engine were used to analyze the effects of varying diesel injection and air-path strategies on the combustion performance, with a focus on the low load operation zone. The results showed that the injection timing, as well as intake charge dilution, can severely promote clean combustion at the low load zone. An early diesel injection can enhance the diesel-natural gas homogeneity within the cylinder and improve the combustion efficiency of the engine. On the other hand, high levels of exhaust gas recirculation (EGR) are mandatory to suppress NOx and further enhance the brake thermal efficiency of the engine.